A highly selective fluorescent probe for human NAD(P)H:quinone oxidoreductase 1 (hNQO1) detection and imaging in living tumor cells. Issue 46 (27th August 2019) - Zhu, Ya; Han, Jialing; Zhang, Qian; Zhao, Zhou; Wang, Jin; Xu, Xiaowei; Hao, Haiping; Zhang, Jun
Abstract : Human NAD(P)H:quinone oxidoreductase (hNQO1) can be used as a biomarker for the early diagnosis of cancer. Abstract : Human NAD(P)H:quinone oxidoreductase (hNQO1) can be used as a biomarker for the early diagnosis of cancer. In this article, a novel fluorescent probe1 for detecting hNQO1 was designed and synthesized by using 2-dicyanomethylene-3-cyano-4, 5, 5-trimethyl-2, 5-dihydrofuran (TCF) derivative (TCF-OH) as a fluorophore and quinone propionic acid (QPA) as a recognition group. The probe, which has high selectivity for hNQO1 and a Stokes shift of about 117 nm, shows a linear relationship with hNQO1 concentrations in the range of 0.25–3 μg ml −1 with the color changes from yellow to red and was successfully applied to intracellular hNQO1 imaging.